PENGEMBANGAN LEMBAR KERJA MAHASISWA BERBASIS PROYEK DENGAN MATERIAL LOKAL PADA PRAKTIKUM BIOKIMIA - Diah K Sari; K A Wancik; Arif R Ibrahim (Chemistry Education Department of Education and Teaching Faculty, 2019)
The student creativity in project-based Biochemistry practicum lectures with local materials can be obtained when teaching materials support the achievement of learning outcomes. The purpose of this study is to develop teaching materials for project-based biochemical practicum with local materials that can enhance student creativity. This research is classified into Development research with the ADDIE development model and Tessmer formative evaluation. The stages of this research consisted of self-evaluation, expert reviews, one to one and small group. The results of this study indicate that teaching materials in the form of Student Work Sheets (LKM) based on projects with local materials have passed the expert review stage by obtaining a material validity score of 0.75 including eligibility criteria, pedagogical validity of 0.77 including eligibility criteria, design of 0.75 including the eligible criteria. Based on one to one trial, it was obtained a value of 90.67% included in the excellent category and a small group obtained a value of 90.67% included in the excellent category. The implementation of LKM based on local material projects has an impact on increasing the creativity of students in the high category.